Efeito de variáveis de paisagem sobre a comunidade de macroinvertebrados em riachos do Baixo Iguaçu, nos municípios de Céu Azul, Santa Tereza do Oeste e Cascavel, no estado do Paraná - Cargnelutti Junior, Julio Cesar (2019)
The lateral dimension of connectivity in a lotic ecosystem was assessed to determine its influence on macroinvertebrate communities. Sampling was conducted in eight microbasins within the Baixo Iguaçu basin in the western region of Paraná, areas that present a gradient of vegetation. To represent the lateral component, physical and chemical water metrics, landscape variables, and bioclimatic data were evaluated. Principal Component Analysis (PCA) was applied to summarize the internal structure of the data, followed by Moran's I index to assess spatial autocorrelation. Generalized Linear Models (GLMs) were used to examine the relationships between the dependent variable (ecological attributes of macroinvertebrates) and independent variables (physical-chemical, bioclimatic, and landscape components). The models were applied to test the hypothesis that the condition of the lateral component predicts the distribution of macroinvertebrate communities, suggesting that community dynamics reflect local stream water variables such as local pollution levels and bed composition, as well as landscape variables, represented here by the amount of vegetation and proximity to Atlantic Forest fragments, and macroecological climatic aspects such as temperature and precipitation. For the conservation and management of lotic ecosystems, we recommend maximizing riparian environments with a focus on headwaters to promote and ensure conditions favorable to the preservation of aquatic biota.